The influence of physical and chemical parameters of modified water glass on the strength of loose self-setting sands with water glass - Kmita, Angelika; Hutera, Barbara (My University, 2012)
An attempt of water glass modifying by 30% water bochmite Al(OH)O solution was undertaken. The flow curves were determined and the binder viscosity estimated from them. The quartz wettability by binders was determined by measuring the wetting angle θ changes with time. Strength properties of moulding sands with fractions of modified binders were verified by checking the tensile strength R$_m^u$ after various hardening times under environmental conditions. The R$_m^u$ value after 24 h of hardening was assumed for the analysis.

W artykule opisano próbę modyfikacji szkła wodnego, trzydziestoprocentowym wodnym roztworem bemitu Al(OH)O. Wyznaczono krzywe płynięcia, z których określono lepkość spoiw. Zwilżalność kwarcu przez spoiwa określono, badając zmiany wartości kąta zwilżania θ w czasie. Właściwości wytrzymałościowe mas z udziałem spoiw modyfikowanych weryfikowano, badając wytrzymałość na rozciąganie R$_m^u$ po różnych czasach utwardzania w warunkach otoczenia. Do analizy przyjęto R$_m^u$ po 24 h utwardzania.
Wpływ parametrów fizykochemicznych zmodyfikowanego szkła wodnego na wytrzymałość mas samoutwardzalnych ze szkłem wodnym
Metallurgy and Foundry Engineering
Keywords: viscosity; wettability; lepkość; modification; zwilżalność; modyfikacja; water glass; szkło wodne